2012
DOI: 10.1901/jeab.2012.98-295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Signaled Delay to Reinforcement in the Previous and Upcoming Ratios on Between‐ratio Pausing in Fixed‐ratio Schedules

Abstract: Domestic hens responded under multiple fixed‐ratio fixed‐ratio schedules with equal fixed ratios. One component provided immediate reinforcement and the other provided reinforcement after a delay, signaled by the offset of the key light. The components were presented quasirandomly so that all four possible transitions occurred in each session. The delay was varied over 0, 4, 8, 16, and 32 s with fixed‐ratio 5 schedules, and over 0, 8 and 32 s with fixed‐ratio 1, 15 and 40 schedules. Main effects of fixed‐ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 22 publications
3
22
0
1
Order By: Relevance
“…Although this was the first study to investigate the effects of negative incentive shifts in food reinforcement on ethanol self-administration, our results are consistent with past findings showing that these transitions generate behavioral disruption in the form of extended pausing (Bejarano et al, 2003;Everly et al, 2014;Galuska & Sawyer, 2017;Galuska et al, 2007;Galuska & Yadon, 2011;Harris et al, 2012;Jessel et al, 2016;Perone & Courtney, 1992;Retzlaff et al, 2017;Wade-Galuska, et al, 2005;Williams et al, 2011). Throughout all conditions in the present study, the negative incentive shift produced the longest pause durations in each rat.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although this was the first study to investigate the effects of negative incentive shifts in food reinforcement on ethanol self-administration, our results are consistent with past findings showing that these transitions generate behavioral disruption in the form of extended pausing (Bejarano et al, 2003;Everly et al, 2014;Galuska & Sawyer, 2017;Galuska et al, 2007;Galuska & Yadon, 2011;Harris et al, 2012;Jessel et al, 2016;Perone & Courtney, 1992;Retzlaff et al, 2017;Wade-Galuska, et al, 2005;Williams et al, 2011). Throughout all conditions in the present study, the negative incentive shift produced the longest pause durations in each rat.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to pigeons (Perone & Courtney, 1992;Retzlaff, Parthum, Pitts, & Hughes, 2017), the effect has been shown in rats working for food (Galuska & Sawyer, 2017;Galuska & Yadon, 2011) and with components varying in force required to execute a lever press (Wade- Galuska, Perone, & Wirth, 2005), domestic hens with reinforcer delay (Harris, Foster, Levine, & Temple, 2012), monkeys responding for self-administered cocaine doses (Galuska, Wade-Galuska, Woods, & Winger, 2007), and humans working for money (Bejarano, Williams, & Perone, 2003;Williams, Saunders, & Perone, 2011) and while transitioning between preferred to less-preferred activities (Jessel, Hanley, & Ghaemmaghani, 2016). In addition to pigeons (Perone & Courtney, 1992;Retzlaff, Parthum, Pitts, & Hughes, 2017), the effect has been shown in rats working for food (Galuska & Sawyer, 2017;Galuska & Yadon, 2011) and with components varying in force required to execute a lever press (Wade- Galuska, Perone, & Wirth, 2005), domestic hens with reinforcer delay (Harris, Foster, Levine, & Temple, 2012), monkeys responding for self-administered cocaine doses (Galuska, Wade-Galuska, Woods, & Winger, 2007), and humans working for money (Bejarano, Williams, & Perone, 2003;Williams, Saunders, & Perone, 2011) and while transitioning between preferred to less-preferred activities (Jessel, Hanley, & Ghaemmaghani, 2016).…”
mentioning
confidence: 99%
“…Thus, just after a more favourable condition, the signal that the transition was to a poorer condition (L–S) resulted in longer PRPs than did the signal that there was an upcoming favorable condition (L–L). Previous studies using multiple schedules have also found longer pauses when poorer conditions are signalled following more favorable conditions (e.g., Galuska et al, ; Galuska & Yadon, ; Harris et al, ; Perone & Courtney, ; Retzlaff et al, ; Wade‐Galuska et al, ; Williams et al, ). Also, as in the present study, PRPs have been reported to be shorter in transitions from poorer conditions (S–L and S–S) than in transitions from more favorable conditions (L–L and L–S).…”
Section: Discussionmentioning
confidence: 92%
“…Harris et al (), using a similar procedure, found a strong effect of an upcoming delay to reinforcement on PRP length but only a weak effect of the delay in the preceding component, suggesting that the upcoming conditions had the greatest effect on the PRP. Here, the mixed schedules allowed examination of the effects of both the preceding reinforcer size and FR size on PRP.…”
Section: Discussionmentioning
confidence: 94%
“…The present experiments replicated the body of literature that has demonstrated extended pausing during signaled transitions from a relatively rich to a relatively lean condition (Everly et al, ; Galuska e al., ; Harris et al, ; Perone & Courtney, ; Wade‐Galuska et al, 2005; Williams et al, ). The present study also extended these findings by demonstrating that the characteristic pattern of extended pausing during signaled rich‐to‐lean transitions occurs when transition‐specific stimuli are used as opposed to only two stimuli (one for the upcoming rich reinforcer and one for the upcoming lean reinforcer).…”
Section: Discussionmentioning
confidence: 99%